2017
DOI: 10.1177/0269881117711712
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of increased openness: Investigating mechanism of action in MDMA-assisted psychotherapy

Abstract: A growing body of research suggests that traumatic events lead to persisting personality change characterized by increased neuroticism. Relevantly, enduring improvements in Post-Traumatic Stress Disorder (PTSD) symptoms have been found in response to 3,4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy. There is evidence that lasting changes in the personality feature of “openness” occur in response to hallucinogens, and that this may potentially act as a therapeutic mechanism of change. The present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(69 citation statements)
references
References 53 publications
2
66
0
1
Order By: Relevance
“…Other reports suggest that MDMA positively biases interpretation of emotional facial expressions, either by enhancing identification of positive expressions, interfering with identification of negative expressions, or both (Bedi et al, 2009;Hysek et al, 2012a;Kirkpatrick et al, 2014b;Wardle and de Wit, 2014a). Negative processing bias has been observed in multiple psychiatric disorders (Bishop, 2007;Rude et al, 2002), including PTSD (Litz et al, 2000), and the positive-biasing effects of MDMA we report here may underlie its effectiveness in a therapeutic context (Mithoefer et al, 2013;Mithoefer et al, 2011;Oehen et al, 2013;Wagner et al, 2017).…”
Section: Discussionsupporting
confidence: 50%
“…Other reports suggest that MDMA positively biases interpretation of emotional facial expressions, either by enhancing identification of positive expressions, interfering with identification of negative expressions, or both (Bedi et al, 2009;Hysek et al, 2012a;Kirkpatrick et al, 2014b;Wardle and de Wit, 2014a). Negative processing bias has been observed in multiple psychiatric disorders (Bishop, 2007;Rude et al, 2002), including PTSD (Litz et al, 2000), and the positive-biasing effects of MDMA we report here may underlie its effectiveness in a therapeutic context (Mithoefer et al, 2013;Mithoefer et al, 2011;Oehen et al, 2013;Wagner et al, 2017).…”
Section: Discussionsupporting
confidence: 50%
“…Increases in Openness have been shown 2 weeks after administration of LSD in healthy individuals ( Lebedev et al, 2016 ). Another study showed that increases in Openness predicted greater reduction in post-traumatic stress disorder symptoms among individuals receiving MDMA-assisted psychotherapy ( Wagner et al, 2017 ). The failure to observe significant increases in Openness in the current study may be attributable to engagement in the program of spiritual practices or to some other aspect of the study design.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, administration of LSD in a brain imaging setting led to discrete increases in Openness scores in healthy volunteers assessed at 2 weeks after the LSD session although this was not replicated in a recent LSD study with longer postsession follow‐up time points (1 month and 12 months) . Recently, administration of the entactogen, 3,4‐methylenedioxy‐methamphetamine (MDMA), in conjunction with psychotherapy has been shown to lead to increases in Openness , as well as decreases in Neuroticism , in patients being treated for post‐traumatic stress disorder . Regular ceremonial use of the psychedelic brew, ayahuasca, was associated with higher Openness scores when compared with matched non‐ayahuasca using controls and self‐reported lifetime recreational psychedelic use correlated positively with Openness scores in a large online survey , as well as in a separate brain imaging trial (D. Erritzoe, under review).…”
Section: Discussionmentioning
confidence: 99%